GLIS1 intervention enhances anti-PD1 therapy for hepatocellular carcinoma by targeting SGK1-STAT3-PD1 pathway. Issue 2 (14th February 2023) - Rong, Dawei; Wang, Yuliang; Liu, Li; Cao, Hengsong; Huang, Tian; Liu, Hanyuan; Hao, Xiaopei; Sun, Guangshun; Sun, Guoqiang; Zheng, Zhiying; Kang, Junwei; Xia, Yongxiang; et al.
Abstract : Background: GLI-similar 1 (GLIS1) is one of of Krüppel-like zinc finger proteins, which are either stimulators or inhibitors of genetic transcription. Nevertheless, its effects on T cell were elusive. Methods: In this study, we intend to explore the effects of GLIS1 on modulating the anticancer potency of CD8 + T cells in hepatocellular carcinoma (HCC). The expression of GLIS1 in CD8 peripheral blood mononuclear cell and CD8 tumor-infiltrating lymphocytes of HCC tissues was validated by quantificational real-time-PCR and flow cytometry. The anticancer potency of CD8 + T cells with GLIS1 knock down was confirmed in C57BL/6 mouse model and HCC patient-derived xenograft mice model. GLIS1 –/– C57BL/6 mice was applied to explore the effects GLIS1 on tumor immune microenvironment. Chromatin immunoprecipitation and RNA transcriptome sequencing analysis were both performed in GLIS1-knock down of CD8 + T cells. Results: GLIS1 was upregulated in exhausted CD8 + T cells in HCC. GLIS1 downregulation in CD8 + T cells repressed cancer development, elevated the infiltrate ability of CD8 + T cells, mitigated CD8 + T cell exhaustion and ameliorated the anti-PD1 reaction of CD8 + T cells in HCC. The causal link beneath this included transcriptional regulation of SGK1-STAT3-PD1 pathway by GLIS1, thereby maintaining the abundant PD1 expression on the surface of CD8 + T cells. Conclusion: Our study revealed that GLIS1 promoted CD8 + T cell exhaustion in HCC through transcriptional regulating SGK1-STAT3-PD1 pathway. Downregulating the expression of GLIS1 in CD8 + T cells exerted an effect with anti-PD1 treatment synergistically, revealing a prospective method for HCC immune therapy.